Importância da gestão do portfólio de produtos e da aplicação de ferramentas de gestão para resolução de problemas em um restaurante de pequeno porte - Lima, Isaias da Silva (Universidade Federal Rural do Semi-Árido, 2019)
The highly competitive market of the contemporary world requires that organizations to be more strategic so that it can obtain competitive advantage. This strategy, at the corporate level, encompasses the management of the product portfolio. This paper presents a case study of a restaurant that underwent a series of operational, stock management, financial and quality problems, aggravated by poor management of its portfolio. This was identified when analyzing, through the Ishikawa Diagram, the causes of the lack of profit in the company. Through the application of the GUT Matrix and the analysis of the prioritization sequence suggested by it, was noticed that many of the problems existed because of this inadequate corporate strategy regarding the products portfolio. The restaurant used a diversification strategy aimed at offering a large amount of meals options to customers, without being able to manage the administrative complexity resulting from it. Then, it was suggested to move to a more specialized strategy, exsiccating the products portfolio. With the support of the ABC Curve was possible to classify the products that should remain and those that could be removed from the menu without causing a great impact on the revenues. Integrated to the reduction, a price adjustment was applied to the remaining products, aiming to solve the problem of the lack of profit initially identified. The results were satisfactory, because the reduction helped to simplify business management throughout the supply chain and the price adjustment contributed to solving of the company financial problems.
Monografia
Keywords: Gestão de portfólio; Curva ABC; Matriz GUT; Diagrama de Ishikawa; Estratégia corporativa; Portfolio management; ABC curve; Matrix GUT; Ishikawa diagram; Corporate strategy; ENGENHARIAS::ENGENHARIA DE PRODUCAO